A new photoelectrochemical reactor designed for solar hydrogen fuel production: Experimental study. (15th March 2022) - Qureshy, Ali M.M.I.; Dincer, Ibrahim
Highlights: Unique meshy dome photoanode for hydrogen production is carried out experimentally. Hydrogen production rate is assessed for vertical and tilted light conditions. Overall system efficiencies of the photoelectrochemical cell are evaluated. The present system achieves promising hydrogen production results. Abstract: A novel photoanode configuration of meshy type dome design is examined to exploit the maximum accessible light during available sun time at any solar rays angle due to its unique structure. This photoanode shape aims to receive the maximum light quantity by utilizing the possible illumination area. Also, the meshy design lets the solar ray spread into the body of the dome photoanode at any solar rays angle. Titanium dioxide is prepared to coat the stainless steel photoanode using the sol–gel dip-coating method. Two concentrations of potassium dioxide solution are used to study the electrolyte solution conductivity effects on the hydrogen production rate and the associated energy and exergy efficiencies. The vertical and tilted light boundaries are studied to evaluate the enhancement of the hydrogen production rate and the corresponding system efficiencies due to the new dome mesh photoanode design. The present experimental results indicate that increasing the solution concentration significantly affects the hydrogen production rates and associated system efficiencies. The greatest hydrogen mass production rates produced at 0.25 M KOH under artificial tilted (45°) and vertical light boundaries are 31.55 µg/s and 32.22 µg/s, respectively. The overall energy and exergy system efficiencies can be reached to be 5.98% and 4.08% under vertical light, while it is 5.89% and 4.02% at tilted light boundaries. The development of the hydrogen production rate obtained at artificial tilted light boundaries changes between 74% and 80% compared to the enhancement which occurred at vertical artificial light boundaries.